Implementasi Website Pendataan Dan Monitoring Kelompok Tani Menggunakan Algoritma Decision Tree - Ruth junia Sinaga; Sondy Campvid Kumajas; Glenn David Paulus Maramis (Universitas Budi Darma, 2026)
This research focuses on developing a web-based information system for data management and monitoring of farmer groups in Minahasa Regency. The system aims to enhance the efficiency, accuracy, and transparency of agricultural data collection and supervision processes. Utilizing technologies such as Laravel framework and Decision Tree algorithms, the system provides real-time data visualization, prediction of assistance needs, and facilitates farmer participation in reporting activities, applying for aid, and accessing training online. The Decision Tree algorithm is employed to generate predictive insights for future aid requirements based on historical data, supporting more informed decision-making by the relevant authorities. The implementation of this system is expected to streamline administrative tasks, improve data accuracy, and promote good governance within the agricultural sector. Overall, this system contributes to advancing digital transformation in agricultural management, enabling better planning, resource allocation, and service delivery for farmers in Minahasa.